A study on energy transfer among limbs in a legged robot locomotion. (December 2018) - Ahmad, Huthaifa; Nakata, Yoshihiro; Nakamura, Yutaka; Ishiguro, Hiroshi
Realizing adaptability to environmental changes requires the robot's body to change according to the environment. From this perspective, several studies have considered variable compliant actuation to change the physical characteristics of the robot as it interacts with the environment. Robots with this ability show a variety of efficient stable motions during contact with the environment. However, having locally variable compliant parts with independent dynamics under the same body may be insufficient for achieving adaptability in diverse environments. To extend the idea of variable compliant actuation, from being used locally to the level of the entire body's dynamics, in this study, we use an actuator network system (ANS). As an approximation of bipedal robots, we developed an eight-legged rimless wheel robot with an ANS that allows energy transfer among limbs through passive interactions among mutually interconnected air cylinders mounted on the robot's legs. We experimentally demonstrated that by using the ANS to realize energy transfer among limbs, the robot performance improved.